Aluminum Consumption and Economic Growth: Evidence from Rich Countries - Jaunky, Vishal (Springer, 2012)
The article attempts to test the aluminum consumption-economic growth nexus for 20 rich economies for the period 1970-2009. Various panel data unit root and cointegration tests are applied. The series are found to be integrated of order one and cointegrated, especially after controlling for cross-sectional dependence. Moreover, the Blundell-Bond system generalized methods-of-moments is employed to conduct a panel causality test in a vector error-correction mechanism setting. Unidirectional causality running from aluminum consumption to real GDP is uncovered in the short-run, while real GDP is found to Granger-cause aluminum consumption in the long-run. Moreover, a 1% increase in real GDP generates an increase of 0.44% in aluminum consumption in the long-run for the whole panel. © 2012 International Association for Mathematical Geology.